The Relationship Between International Financial Reporting Standards, Carbon Emissions, and R&D Expenditures: Evidence from European Manufacturing Firms - Apergis, Nicholas; Eleftheriou, Sofia; Payne, James (Elsevier, 2013)
This study examines the impact of research and development (R&D) expenditures on carbon dioxide (CO2) emissions prior to and under the mandatory adoption of International Financial Reporting Standards at the firm level within the manufacturing sectors of three European countries, i.e. Germany, France and the U.K. Estimation of a threshold autoregressive model using quarterly data from 1998 to 2011 reveals that in the post-IFRS mandatory adoption year R&D expenditures show a reduction in CO2 emissions to firms, i.e. rising CO2 abatement. This is likely due to the presence of incentives provided by the new accounting disclosure regime. Our results remain robust in terms of a sector analysis, firm size, and the introduction of the European Union Emission Trading Scheme (EU-ETS) across the three countries.